Comparative analysis and implementation of AI algorithms and NN model in process scheduling algorithm - Niloy, Maharshi; Moni, Md. Moynul Asik; Khan, Farah Jasmin; Chowdhury, Aquibul Haq; Juboraj, Md. Fahmid-Ul-Alam (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.